Hepatoprotective effect of Solanum surattense leaf extract against chemical- induced oxidative and apoptotic injury in rats - Mohammad K. Parvez; Mohammed S. Al-Dosari; Ahmed H. Arbab; Perwez Alam; Mansour S. Alsaid; Azmat A. Khan (BMC, 2019)
Abstract Background Of over 35 Saudi plants traditionally used to treat liver disorders, majority still lack scientific validations. We therefore, evaluated the anti-oxidative, anti-apoptotic and hepatoprotective potential of Solanum surattense leaves total ethanol-extract (SSEE). Methods The cytoprotective (4,5-dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide/ MTT assay) and anti-apoptotic (caspase-3/7) potential of SSEE (25-200 μg/mL) were assessed in cultured HepG2 cells against dichlorofluorescein (DCFH)-induced toxicity. The hepatoprotective salutation of SSEE (100 and 200 mg/kg.bw/day) in carbon tetrachloride (CCl4)-intoxicated rats was evaluated by serum biochemistry and histopathology. The anti-oxidative activity of SSEE (31.25-500 μg/mL) was tested by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging and linoleic acid bleaching assays. Also, SSEE was subjected to qualitative phytochemical analysis, and standardized by validated high-performance liquid chromatography (HPTLC). Results SSEE at doses 50, 100 and 200 μg/mL showed HepG2 cell proliferative and protective potential by about 61.0, 67.2 and 95%, respectively through inhibition of caspase-3/7 against DCFH-toxicity. In CCl4-injured rats, SSEE (200 mg/kg) significantly (P < 0.001) normalized serum transaminases, alkaline phosphatase, bilirubin, cholesterol, triglycerides, and total protein, including tissue malondialdehyde and nonprotein sulfhydryls levels, supported by the liver histopathology. SSEE further showed strong in vitro anti-oxidative and anti-lipid peroxidative activities, evidenced by the presence of alkaloids, flavonoids, tannins, sterols and saponins. Identification of β-sitosterol (3.46 μg/mg) strongly supported the anti-oxidative and hepatoprotective salutation of SSEE. Conclusion Our findings suggest the therapeutic potential of S. surattense against chemical-induced oxidative stress and liver damage. However, isolation of the active principles and elucidation of mechanism of action remain to be addressed.